Legal Implications On Privacy And Security Issues On The Internet - Veloo, Veni (2002)
In Asian countries, many do not have privacy protection laws so far. In the modern world, privacy is equated with security of personal information. There are federal and common law protection on privacy issues in US; however on legal protection on security issues, there are different opinions on strong encryption and the US stand on these policies. There are also "digital signature legislation" in both US and some Asian countries including Malaysian. With the advent of the digital era, the conception of digital payment begins : bringing crimes online to a rise. It is clear that current regulations are in their infancy and does not seem to overcome these security problems effectively.